The time-varying NAIRU and potential output in Finland - Chris-Marie Rasi; Jan-Markus Viikari (Bank of Finland, 1998)
This study presents statistical estimates of Non Accelerating Inflation Rate of Unemployment, or NAIRU, and potential output in Finland.The estimates are obtained by applying the structural time series/unobserved components method to quarterly data on inflation, rate of unemployment, aggregate production and a number of auxiliary variables covering the period 1982:1-1996:4.According to the basic idea underlying these methods, noisy estimates of the unobserved NAIRU and potential output can be obtained from the so called measurement equations, which in the present study are provided by the now standard specifications of the Okun's law and Phillips-curve.To pin down the dynamics of the unobserved components the study assumes that they are driven by stochastic trends.One of the main features of the method applied in the study is the system estimation of the NAIRU and potential output time seria along with other parameters.According to the results NAIRU and potential output variate in the long run less than the actual unemployment rate and output.Until the latter part of 1991 NAIRU has been above the unemployment rate.After this the NAIRU has remained clearly below the unemployment rate although it has risen trendwise to a level between 8 and 9.5 per cent in the 1990ies.
URN:NBN:fi:bof-20140807640
Keywords: 330; NAIRU; potential output; Phillips curve; structural time series models; unobserved components method